Uv?vis spectroscopy for simple chloride content analysis in edible oil using charged amino-functionalized carbon quantum dots fluorophore reagent - Abu Bakar M.H.; Azeman N.H.; Mobarak N.N.; Nazri N.A.A.; Daniyal W.M.E.M.M.; Othman M.Q.; Abdullah F.; Bakar A.A.A. (Elsevier B.V., 2025)
The utilization of UV?Vis spectroscopy with amino-functionalized carbon quantum dots (NCQD) as a positive fluorophore reagent for chloride sensing in oil marks a notable advancement in analytical spectroscopy chemistry. This approach streamlines the detection process by eliminating the need for lengthy procedures and pretreatment steps typically associated with chloride detection in edible oil. By incorporating NCQD in chloride detection within the oil matrix, the wavelength analysis transitions from the UV to the visible region. This shift eliminates interference from oil matrix interactions, ensuring more accurate results. Molecular analysis of NCQD reveals significant shifts in its Fourier Transformation Infrared and photoluminescence spectroscopy peaks due to interaction with chloride in edible oil. It has two impressive sensitivity ranges spanning from 0.1?1.0 to 1.0?8.0 ppm, with a value of ?0.4656 au. ppm?1 (R2 = 0.998) and ?0.0361 au. ppm?1 (R2 = 0.931), respectively, the technique meets regulatory standards while achieving a low limit of detection (LOD) of 0.1 ppm. This places it on par with conventional methods and commercial sensors. The NCQD-UV?Vis spectroscopy method not only enhances the efficiency and accuracy of chloride detection but also holds promise for various industrial applications requiring simple and precise monitoring of chloride levels in oil samples. ? 2024 Elsevier B.V.